(untitled) (World Bulletin of Management and Law, 2026)
This article examines the need to modernize the Law of the Republic of Uzbekistan “On Guardianship and Trusteeship” in response to contemporary social changes, digital transformation, and international legal standards. The study analyzes the existing legal framework through comparative legal, institutional, and international approaches, with particular attention to digitalization, electronic governance, and the potential use of artificial intelligence in guardianship practices. Based on foreign experience from Europe, the United States, Russia, and Kazakhstan, the article identifies key shortcomings in current legislation and proposes evidence-based recommendations aimed at enhancing transparency, efficiency, and the protection of the rights of children and other persons in need of guardianship.